THE HOLOCENE PALYNOSTRATIGRAPHY AND GEOCHRONOLOGY OF LACUSTRINE-PALUSTRINE DEPOSITS IN THE KOLA PENINSULA - Kremenetskii K.V.; Patyk-Kara N.G.; Goryachkin S.V. (My University, 1998)
The studied objects represent the lacustrine bottom deposits in the southeast of the Kola Peninsula and the peat bed in the Cape Rybachii, exemplifying the northernmost occurrence of this substance in the European part of Russia. A detailed radiocarbon dating and palynological analysis provided grounds to establish the Holocene chrono- and climatostratigraphy of the region and to correlate the studied sections with coeval deposits in Scandinavia. Sedimentation in the lakes commenced in the region 11 000-10 000 years ago. The pine species spread over the Kola Peninsula 9000-7000 years ago. The peat accumulation was initiated here 8000-7500 years ago. The birch tundra forests advanced up to the Barents Sea coast 6000-5000/4500 years ago. The northern forest boundary retreated southward after the climate deteriorated 4500 years ago. When the pine forest areas decreased, peat bogs became more widespread in the southeastern Kola Peninsula, and the tundra belt appeared at the coast of the Barents Sea. Spruce trees arrived at their northern distribution limit in the peninsula about 3500 years ago. The current structure of the vegetation cover was formed during the last 2500-2000 years.
Keywords: Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен